Hearing-friendly audio signal synthesis system for tinnitus therapy - Lin, Sun-Ting; Wang, Chih-Hsing; Yang, Cheng-Fu (Microsystem technologies : sensors, actuators, systems integration, 2021)
An audio signal synthesis system for otolaryngologists to use in treating tinnitus is proposed. The system parameters can be adjusted so that patients and clinicians can choose from various audio signal types, or also called music, to improve the treatment effect. Chaos theory forms the basis of the system and is used to generate a source stream of random rhythms and pitches. By using statistical methods, the differences between sequential tones are limited to within 0.5–3 standard deviations of the selected bandwidth’s pitch difference distribution. At the same time, a function to adjust the center position is included to avoid monotonous tones. In addition to creating an adjustable music synthesizer to achieve the goal of hearing-friendly tinnitus therapy, we performed spectrum analysis on various generated music sequences to compare the spectrum formed by different audio generation methods. In the future, we plan to work with otolaryngologists to explore the relationship between spectrum distribution and effective therapeutic settings.